TINJAUAN YURIDIS PENERAPAN ASAS NON-SELF INCRIMINATION TERHADAP SAKSI MAHKOTA DALAM HUKUM ACARA PIDANA INDONESIA - Simanjuntak, Febri Nolin; Indra, Mexsasai; Erdiansyah, Erdiansyah (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2019)
In criminal procedural law, witnesses can be divided into several forms, one of which is a crownwitness or a crown witness. The crown witness is a witness originating from or taken from one of the othersuspects or defendants who jointly committed a criminal act in the event that the witness was given a crown.Crown witnesses themselves are not regulated in detail in the Criminal Procedure Code. To be able to makea suspect or defendant as a crown witness must be carried out through the procedure of solving the case filewhich is the authority of the Public Prosecutor. The use of crown witnesses in uncovering a case still posesa problem, because the use of a crown witness is not in accordance with the system of evidence and themodel of the criminal justice system in force in Indonesia.The research entitled